I'll be waiting : a novel [large type] - Armstrong, Kelley (Thorndike Press large print high octane., 2025)
Nicola Laughton never expected to see adulthood, being diagnosed with Cystic Fibrosis as a child. Medical advances helped her survive into her 30s when she met Anton. Months after they married, Anton died in a horrible car crash, but lived long enough to utter five words to her, 'I'll be waiting for you'. That final private moment became public when someone from the crash scene took it to the press - the terminally ill woman holding her dying husband as he promised to wait for her on the other side. Worse, that person claimed it wasn't Anton who said the words but his ghost, hovering over his body. Since their story went public, Nicola has been hounded by spiritualists promising closure. In the hopes of stopping her downward spiral, friends and family find a reputable medium - a professor of parapsychology. The medium barely has time to begin his work before things start happening. Nicola hears footsteps and voices and the creak of an old dumbwaiter ... in an empty shaft, and is haunted by nightmares of her past. Because, unbeknownst to the others, this isn't her first time contacting the dead. And Nicola isn't her real name.